SNX8 Enhances Non-amyloidogenic APP Trafficking and Attenuates Aβ Accumulation and Memory Deficits in an AD Mouse - Xie, Yongzhuang; Niu, Mengxi; Ji, Chengxiang; Huang, Timothy Y.; Zhang, Cuilin; Tian, Ye; Shi, Zhun; Wang, Chen; Zhao, Yingjun; Luo, Hong; Can, Dan; Xu, Huaxi; et al. (Frontiers in Cellular Neuroscience, 2019)
Dysregulation of various APP trafficking components in the endosome has been previously implicated in Alzheimer’s disease (AD). Although single nucleotide polymorphisms within the gene locus encoding the endosomal component, SNX8 have been previously associated with AD, how SNX8 levels are altered and its contribution to AD onset is currently unknown. Here, we observe decreased expression of SNX8 in human AD and AD mouse brain. SNX8 predominantly localized to early and late endosomes, where SNX8 overexpression enhanced total APP levels, cell surface APP distribution and consequent soluble APPα cleavage. SNX8 depletion resulted in elevated β-amyloid (Aβ) levels, while SNX8 overexpression reduced Aβ levels in cells and in an APP/PS1 AD mouse model. Importantly, SNX8 overexpression rescued cognitive impairment in APP/PS1 mice. Together, these results implicate a neuroprotective role for SNX8 in enhancing non-amyloidogenic APP trafficking and processing pathways. Given that endosomal dysfunction is an early event in AD, restoration of dysfunctional endosomal components such as SNX8 may be beneficial in future therapeutic strategies.